Channel of viral DNA packaging motor for real time kinetic analysis of peptide oxidation states. (May 2017) - Wang, Shaoying; Zhou, Zhi; Zhao, Zhengyi; Zhang, Hui; Haque, Farzin; Guo, Peixuan
Abstract: Nanopore technology has become a powerful tool in single molecule sensing, and protein nanopores appear to be more advantageous than synthetic counterparts with regards to channel amenability, structure homogeneity, and production reproducibility. However, the diameter of most of the well-studied protein nanopores is too small to allow the passage of protein or peptides that are typically in multiple nanometers scale. The portal channel from bacteriophage SPP1 has a large channel size that allows the translocation of peptides with higher ordered structures. Utilizing single channel conductance assay and optical single molecule imaging, we observed translocation of peptides and quantitatively analyzed the dynamics of peptide oligomeric states in real-time at single molecule level. The oxidative and the reduced states of peptides were clearly differentiated based on their characteristic electronic signatures. A similar Gibbs free energy (ΔG 0 ) was obtained when different concentrations of substrates were applied, suggesting that the use of SPP1 nanopore for real-time quantification of peptide oligomeric states is feasible. With the intrinsic nature of size and conjugation amenability, the SPP1 nanopore has the potential for development into a tool for the quantification of peptide and protein structures in real time.